Correlating ultrasonic pulse velocity to the compressive strength of cement-stabilized soil - Tabilas, Danilo D. Jr
Cement-stabilized soil is a mixture of pulverized soil, cement, and water compacted to a high density to form a strong and durable material that is commonly used in construction of road bases, embankment slopes, earth dam cores, and reinforcement of load-bearing layers. Its properties and behavior are time-dependent and they commonly require time-consuming destructive tests to be characterized. The main objective of this study was to investigate the relationship of compressional wave velocity to cement stabilized soil. Ultrasonic pulse velocity test was conducted on soil-cement samples cured at 7, 14, and 28 days to determine the compressional wave velocity or P-wave velocity. Then, samples were subjected to unconfined compression test to measure the unconfined compressive strength. Samples were made with varied maximum particle sizes to examine any changes in the strength and wave velocity. Also, ultrasonic tests were done on soil-cement mixtures to observe the variation of ultrasonic wave velocity during the strength development period. Results of the study showed that compressional wave velocity and unconfined compressive strength of the samples had a moderate positive linear relationship yielding a coefficient of correlation of R=0.4215. Additionally, data indicated that samples made with smaller maximum particle-size soil yielded higher wave velocities and higher compressive strength. Moreover, statistical analysis revealed that there was no significant relationship between curing age of the samples and compressional wave velocity. The research that has been undertaken has explored the use of nondestructive testing in soils that would be beneficial to the advancement of nondestructive strength assessment and quality control of soils and has aided in addressing the gap in literature about nondestructive testing of soils in the Philippine setting.